Biochemistry : essential concepts - Hardin, Charles (Oxford University Press, 2013)
"One-semester biochemistry courses are notorious for overwhelming students with the magnitude of material covered in their texts and lectures. Biochemistry: Essential Concepts distills the basic ideas covered in a one-semester course without the extraneous details that burden most texts. Authors Charles Hardin and James Knopp demonstrate the core concepts of biochemistry--including cell biology, amino acids, metabolism, and DNA--in a variety of real-world contexts. With the last forty percent of the text devoted to review questions and practice tests, Biochemistry: Essential Concepts equips students for success in the one-semester biochemistry course and prepares them for their future studies and careers."--Publisher's website
Keywords: Biochemistry -- Outlines, syllabi, etc.; elektronické knihy; electronic books